2017
DOI: 10.1002/elan.201600627
|View full text |Cite
|
Sign up to set email alerts
|

Covalently Anchored p‐Aminobenzene Sulfonate Multilayer on a Graphite Pencil Lead Electrode: A Highly Selective Electrochemical Sensor for Dopamine

Abstract: An electrochemical sensor for dopamine (DA) has been developed based on the electrografting of 4‐aminobenzene sulfonic acid (4‐ABSA) onto the graphite pencil lead electrode (GPLE). The process of covalent anchoring and presence of 4‐ABSA on the GPLE was studied using cyclic voltammetry and electrochemical impedance spectroscopy. Electrochemical behaviour of the sensor towards DA, ascorbic acid (AA), and uric acid (UA) was studied in detail in phosphate buffer of pH 7. After optimizing the various parameters th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…[ 18‐19 ] The modifiers that are used to modify electrodes include but not limited to nanomaterials, conductive polymers, metals, metal oxides, ionic liquids and more commonly the composite materials. [ 20‐23 ] Metal‐organic frameworks (MOFs) are a new class of crystalline porous nanomaterials, which are usually used as an electrode modifier. [ 24‐27 ] MOFs have drawn significant attention in terms of adsorption, separation, gas storage and catalysis.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…[ 18‐19 ] The modifiers that are used to modify electrodes include but not limited to nanomaterials, conductive polymers, metals, metal oxides, ionic liquids and more commonly the composite materials. [ 20‐23 ] Metal‐organic frameworks (MOFs) are a new class of crystalline porous nanomaterials, which are usually used as an electrode modifier. [ 24‐27 ] MOFs have drawn significant attention in terms of adsorption, separation, gas storage and catalysis.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…In general, covalently linked modified electrodes, such as amide bond formation via carboxylic acid and amine functional group interaction, express good stability and selectivity towards desired electroanalytical applications. In 2017, Devaramani et al reported a 4-aminobenzene sulfate (4-ABSA) modified PGE (2 mm) as an electrochemical for DA sensor [ 40 ]. In this procedure, a pristine PGE was directly exposed into a 0.1 M KCl solution containing 5 mM of 4-ABSA solution and electro-polymerized in a window of +0.5 to +1.5 V at 10 mVs −1 in 0.1 M KCl.…”
Section: Activated Pencil Graphite Modified Electrodes For Electroche...mentioning
confidence: 99%
“…It needs surface pretreatment for the activation (PGE*, * = activated surface), which may result in an improved electroconductivity, electroactive surface area and adsorptive nature. For the activation of PGE, anodization [ 39 ], modification of organic polymers [ 40 ], metal oxides [ 41 ], nanoparticles [ 42 ] and nanomaterial [ 43 ] have been referred. The database used in the search of the research articles is sourced from Scopus ® with keywords in the title as “pencil, dopamine”.…”
Section: Introductionmentioning
confidence: 99%
“…PGE has unique properties such as stability, mechanical rigidity, wide potential window, good adsorption of the analyte, desirable for electrodes assembling, and some advantages when compared to traditional electrodes such as simplicity and low cost of fabrication, disposability and renewable surface, overcoming the issue fouling surface [14]. In recent years, various electroanalytical applications using PGE with satisfactory performance has been highlighted in the scientific literature [7a–c, 15]. Although the above‐mentioned modified electrode for the determination of CIP demonstrated very good sensitivity and a low detection limit, these methods are time‐consuming due to the preparation of modified electrodes and the electrode materials are more expensive than PGEs.…”
Section: Introductionmentioning
confidence: 99%